(untitled) (Bulletin KNOB, 1990)
Restoring the Church of Our Lady at Dordrecht in 1903 Jos.Th.J. Cuypers and town-architect H.W. Veth provided every window with stone tracery and montants again. The stained-glass which had been removed with most of the traceries during the 17th and 18th centuries was renewed as well. The general activities on the choir’s both and the chapels’ window-panes continually proceeded in consultation with the Government Committee which functioned as an independent consultative council to the Minister of the Interior. Dr. P. J. H. Cuypers being an important member of this committee this article makes researches into his influence on the choice of style and subject of these stained-glass windows. In the choir geometrically set up floral motifs and symbols of professions contrast sharply with the luxuriant intertwined leafs and tendrils in Dutch Art Nouveau style. Cuypers disapproved of the windows with the abstract rigid design (1903-04) because they were lacking in the simplicity and colour range of their medieval predecessors. The stained-glass windows in the Choir of Our Lady show stylistic differences as well. Designed by H. Veldhuis and executed by J.L. Schouten the three windowpanes in the Chapel of Jerusalem (1909) represent events from Dordrecht’s history in a historizing-eclectic way after 16th/17th century paintings. Cuypers severely criticized subject and style as unfit to the history of the church which criticism was opposed by the chairman of the Restoration-committee Mr. J.C. Overvoorde. Cuypers being in favour of the mosaic-like character of the 12th and 13th century art of glass-painting, a note by J.L. Schouten, defends the picturesque appearance of these windows comparing them with the beautiful 16th century window-panes in the Church of St. John at Gouda which also describe monumental historical events. The same discussion reflects the argumentation on the choice of subject and style at a Protestant and a Catholic church. Cuypers considering transparency and decorativeness the most important characteristics of the art of glass-painting very much rejected their colour range and representations because they did not harmonize with the 15th century monument they had to adorn and complete. The artist has to adjust himself to the style of the monument in order to acquire harmony. Therefore the stained-glass windows of 1912 show a completely different style. Again designed by H. Veldhuis and executed by J.L. Schouten the window-panes in the Chapel of Meerdervoort show central themes of the life of Christ with appropriate symbolism and cross references to texts. Influenced by the oeuvre of contemporary Symbolists the medieval style of these window-panes has been stylized by geometrical forms and abstract elements. The window-pane in the Chapel of St. Pancras (1914) was designed by Cuypers himself although the execution rested with J.L. Schouten again. The confrontation of Pancratius with the Roman emperor has been represented within a classical setting which contrasts remarkably with the architectural framing of medieval motifs designed to harmonize with the building’s style. The classical elements, the style and spatial illusion are highly representative to the - at the time already conventional - 19th century art of glass-painting. Thus the conflicting opinions and following choices and actions by Cuypers, Overvoerde and Schouten reflect Dutch problemacy on the art of glass-painting of about 1910. While discussion focused on the choice of the medieval, 16th/17th century or modern style results finally also show the confrontation of an elder and a younger generation both mostly following their own personal taste.